The Teacher’s Spirit as The Core: The Philosophy of Professionalism in Imam Zarkasyi’s Thought - Kurniawan Dwi Saputra (At-Ta'dib, 2022)
One of the main problems of Indonesian education is the low professionalism of teachers. Many teachers in the country have low professional competence. Moreover, the low competence of teachers is mostly caused by a lack of motivation in carrying out work and improving self-competencies. In order to provide a perspective related to this problem, this study aims to analyze the concept of professionalism based on Imam Zarkasyi's thoughts about the figure of teacher. The type of research is library research with the data derived from the literature sources. The data analysis technique used the descriptive qualitative method and data validation used the source triangulation technique. This study found that in Imam Zarkasyi's thought, the essence of teacher professionalism lies in the spiritual value embodied by the figure of the teacher. From the so-called the ruh mudarris, the other competencies that support the teacher's activities are built, from mastery of maddah (material) that reflects professional competence, mastery of methodical skills (al-tariqah) or pedagogical competence, to teacher’s etiquette and character as personality and social competence. Imam Zarkasyi's thinking reflects the paradigm of professionalism that is socially oriented and accommodates spiritual values.